The Assessing the Impact of Business Risk on Financial Performance: Analysis of Capital Structure Moderation in the Indonesian Pharmaceutical Industry: Menilai Dampak Risiko Bisnis terhadap Kinerja Keuangan: Analisis Moderasi Struktur Modal pada Industri Farmasi Indonesia - wiwit hariyanto; Ruci Arizanda Rahayu; Fityan Izza Noor Abidin; Endra Wahyu Ningdiyah (Universitas PGRI Madiun, 2026)
This study aims to analyze the effect of Business Risk on Financial Performance with Capital Structure as a moderating variable in pharmaceutical companies listed on the Indonesia Stock Exchange during the 2018–2024 period. Financial Performance was proxied by Return on Equity (ROE), Business Risk was proxied by Business Risk (BRISK), while Capital Structure was proxied by Debt to Equity Ratio (DER). This research employed a quantitative approach with a causal associative research design. The sampling technique used purposive sampling, resulting in 8 pharmaceutical companies with a total of 56 observations. Data analysis was conducted using Partial Least Square (PLS) with SmartPLS software. The results indicate that Business Risk has a positive and significant effect on Financial Performance. In addition, Capital Structure is able to moderate and strengthen the influence of Business Risk on Financial Performance. These findings imply that effective business risk management and optimal capital structure policies can improve the financial performance of pharmaceutical companies in Indonesia